2009
DOI: 10.1111/j.1755-3768.2008.01170.x
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning protects the retinal pigment epithelium cells from oxidative stress‐induced cell death

Abstract: ABSTRACT.Purpose: The cytotoxic effects of oxidative stress, which play an important role in ocular diseases, are well known. In this study, we investigated the effect of non-lethal doses of oxidative stress on various cell functions, namely cell viability, cell attachment and cell migration in a widely used retinal pigment epithelium (RPE) cell line (ARPE-19). Methods: A single exposure to various concentrations of hydrogen peroxide (H 2 O 2 ) was used to establish a dose response for H 2 O 2 -induced cell de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…Formalin-fixed, paraffin-embedded (FFPE) tissues (n = 58, ages [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] were sectioned at 5 mm, transferred onto Fisher Superfrost Plus slides, deparaffinized, rehydrated and then subjected to antigen retrieval using Vector Antigen Unmasking Solution, pH 6.0 (Vector Laboratories) for 1 h at 80°C. The sections were incubated in a humidity chamber overnight at 4°C with a mouse monoclonal antibody developed against 4HNE-modified low-density lipoprotein (clone NA59) that binds to lysine adducts of 4HNE.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Formalin-fixed, paraffin-embedded (FFPE) tissues (n = 58, ages [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] were sectioned at 5 mm, transferred onto Fisher Superfrost Plus slides, deparaffinized, rehydrated and then subjected to antigen retrieval using Vector Antigen Unmasking Solution, pH 6.0 (Vector Laboratories) for 1 h at 80°C. The sections were incubated in a humidity chamber overnight at 4°C with a mouse monoclonal antibody developed against 4HNE-modified low-density lipoprotein (clone NA59) that binds to lysine adducts of 4HNE.…”
Section: Methodsmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27] Of special relevance to carcinogenesis are adaptive responses to chronic oxidative stress identified that might lead to the evolution of subpopulations of cells that can evade mechanisms that limit the propagation of cells with oxidatively-damaged DNA, notably, increased resistance to apoptosis [28][29][30][31] and tolerance to DNA damage. [32][33][34] The chronic oxidative stress final-common-path hypothesis, referred to above, is based on the following considerations.…”
Section: Do Not Distributementioning
confidence: 99%
“…The majority of studies have experimented with hypoxia or anoxia alone, termed hypoxic preconditioning (HPC), while others include nutrient deprivation. In some studies, hydrogen peroxide (H 2 O 2 ) was used to simulate the ischaemic condition of oxidative stress (Li et al, 2009;Sharma et al, 2008). Furthermore, different HPC protocols, from the classical multiple cycles of brief hypoxia with intermittent reoxygenation to a single long-term exposure to hypoxia, have been employed to demonstrate the cytoprotective effect of HPC on stem and progenitor cells in vitro.…”
Section: Ex Vivo Ischaemic and Hypoxic Preconditioning Of Stem Cellsmentioning
confidence: 99%
“…Preconditioning of model cells of retinal pigment epithelium with non-lethal oxidative stress protects these cells from cell death induced by oxidative-stress (Sharma et al, 2009). The cell line ARPE-19 was used to mimick the conditions of oxidative stress, which is encountered by retinal cells transplanted for repairing the age-related macular degeneration.…”
Section: Cellular Stress Responses In Regenerative Medicinementioning
confidence: 99%
“…There are examples of pre-treatments of cells to manipulate stress response pathways that minimise cellular damage and improve the transplantation outcome. Preconditioning of model cells of retinal pigment epithelium with non-lethal oxidative stress protects these cells from cell death induced by oxidative-stress (Sharma et al, 2009). The cell line ARPE-19 was used to mimick the conditions of oxidative stress, which is encountered by retinal cells transplanted for repairing the age-related macular degeneration.…”
Section: Cellular Stress Responses In Regenerative Medicinementioning
confidence: 99%